2010
DOI: 10.4236/wet.2010.12014
|View full text |Cite
|
Sign up to set email alerts
|

Rain Attenuation at Terahertz

Abstract: Rain attenuation values were calculated using empirical raindrop-size distributions, which were, Marshall-Palmer (M-P), Best, Polyakova-Shifrin (P-S) and Weibull raindrop-size distributions, and also calculated using a specific rain attenuation model for prediction methods recommended by ITU-R. Measurements of Terahertz wave taken at 313 GHz (0.96 mm) were compared with our calculations. Results showed that the propagation experiment was in very good agreement with a calculation from the specific attenuation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 11 publications
(12 reference statements)
1
9
0
Order By: Relevance
“…The measurements of rain attenuation in [22], [23] indicate that the propagation experiment is in very good agreement with the calculation from the specific attenuation model for use in prediction method by ITU-R P.838-3 [24]. In addition, it can be concluded that the rain attenuation of THz wave is little affected by temperature.…”
Section: A Rain Attenuationsupporting
confidence: 64%
See 1 more Smart Citation
“…The measurements of rain attenuation in [22], [23] indicate that the propagation experiment is in very good agreement with the calculation from the specific attenuation model for use in prediction method by ITU-R P.838-3 [24]. In addition, it can be concluded that the rain attenuation of THz wave is little affected by temperature.…”
Section: A Rain Attenuationsupporting
confidence: 64%
“…In addition, the precipitation attenuation caused by the interaction between the propagating waves and the raindrops and snowflakes has been studied in few experimental studies and limited lectures for the case of outdoor tests in adverse weather conditions which may pose a threat to sensitive measurement equipment. S.Ishii et al in [22], [23] calculated the rain attenuation at 313 GHz under a rainfall rate of up to 12 mm/h and at 355.2 GHz under a rainfall intensities up to 25 mm/h, where it was found that the prediction of ITU-R P.838-3 [24] has a good agreement with the results of these propagation experiment. In [25], the authors concluded that the rain attenuation of the THz wave increases with the increasing rainfall intensity, and the temperature has little effect on the rain attenuation.…”
Section: Introductionmentioning
confidence: 89%
“…Encoding information that used NRZ encoding technique, whose "1" represents a significant bit and "0" for another considerable bit. The yield of the driver is also given to the subsystem of another MZM that has information levers [20]. The laser signal propagates through FSO with transmitter power 35 dBm and the divergence angle was 2 mrad.…”
Section: Design and Simulations Of Mimo Techniquementioning
confidence: 99%
“…where h 1 , h 2 , and h 3 are defined in (11)- (13), respectively, and σ w is the same as in (14). Parameter B is introduced for the accuracy improvement of the window frequencies and C is for the central frequencies of the rotational and vibrational absorption lines.…”
Section: Modified Model For Water Vapourmentioning
confidence: 99%
“…Experiments for snow and rain attenuation at frequencies of 96, 140, and 225 GHz were carried out by researchers of the Cold Regions Research and Engineering Laboratory in 1988 [13]. Ishii and colleagues measured the rain attenuation for frequencies of 313 and 355 GHz in 2010 [14] and 2011 [15], respectively.…”
Section: Introductionmentioning
confidence: 99%